Methods of risk prediction and monitoring of treatment response rate of bleedings from esophageal varices in patients with liver cirrhosis - D. V. Garbuzenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To describe methods of bleeding from varicose esophageal veins (VEV) risk estimation in patients with liver cirrhosis and to demonstrate a role of some of them in monitoring of treatment response rate.Original positions. Gastroduodenoscopy and hepatic venous pressure gradient measurement remain to be the standard methods of screening diagnostics of patients with liver cirrhosis for estimation of VEV bleeding risk nowadays. Their inherent disadvantages promoted studying of sensitivity and specificity of other predictors of this complication, as well as technologies estimating severity of portal hypertension, such as capsule endoscopy, Doppler ultrasound, multispiral computer tomography, non-invasive methods of liver fibrosis diagnostics and of some others.Conclusion. Optimization of known methods of assessment of portal hypertension, and development of new, pathophysiologically based methods, allows to increase efficacy of VEV bleedings prophylaxis in patients with liver cirrhosis.